Experimental implementation of dynamic spectrum access for video transmission using USRP - Tahir, Mohammad; Mohamad, Hafizal; Ramli, Nordin; Jarot, Sigit Puspito Wigati (2012)
In this paper we present the experimental implementation of dynamic spectrum access (DSA) algorithm using universal software radio peripheral (USRP) and GNU Radio. The setup contains two primary users and two cognitive radios or secondary users. One primary user is fixed and the other is allowed to change its position randomly. Depending upon the position of the primary user the cognitive user will use the spectrum band where the detected energy is below certain predefined threshold level. The cognitive radio users are also programmed to operate independently without interfering with each other using energy detection algorithm for spectrum sensing. The modulation scheme is set to GMSK for secondary user performing data transmission. This experimental setup is used to analyze the quality of video transmission using DSA which provides the insight regarding the possibility of using free spectrum space to improve the performance of the system and its advantage over a non-DSA system. From the experiment it is shown that under congestion and interference DSA perform better than a non- DSA system.